COLREGs Experience-Based Real-Time Route Planning of Intelligent Ship - Yu Peng (IEEE Access, 2023)
The route planning of intelligent ship has been studied a lot, especially in the dynamic planning of collision avoidance, but it is still faced with some difficulties, such as complex model structure, poor compatibility of collision avoidance rules, difficult to practice and so on. Therefore, this paper adopts the integration of field model theory and COLREGs for real-time ship route planning, taking into account the model efficiency and application value. It uses FM algorithm as the basic route planning algorithm, introducing the virtual electric field model to construct the ship navigation situation, and gives the guidance strategy of collision avoidance behavior under different encounter situations considering the COLREGs and daily navigation experience, which integrates it into the field model to form a real-time collision avoidance adjustment route planning algorithm. The proposed algorithm has been compared and verified by simulation in multiple scenes, it is worth mentioning that the algorithm can potentially be developed to advance collision-free route planning in unconstructed environment.